Paraffin induced sclerosing lipogranuloma of eyelids and anterior orbit following endonasal sinus surgery. Issue 1 (January 1994) - Witschel, H; Geiger, K
Abstract : During the past 5 years we have seen 10 patients who had developed sclerosing lipogranuloma of the lid and orbit after endonasal sinus surgery with subsequent ipsilateral monocular haematoma. The histopathological examination of all and the additional nuclear magnetic resonance spectroscopic examination of four surgical specimens in combination with the typical clinical course led to the conclusion that the granulomas were caused by small paraffin droplets. These in turn stemmed from the ointment plugs applied to the sinuses at the end of the operation, and were washed out into the surrounding tissues by the postoperative haemorrhage. As the chronic and recurring granulomas can lead to considerable cosmetic and functional impairment, the application of ointment plugs at the end of sinus surgery should be abandoned, especially when peri- or postoperative bleeding occurs.